PENGARUH BERAT LABUR DAN JENIS KAYU TERHADAP SIFAT FISIKA DAN MEKANIKA PAPAN LAMINASI - Febriana Tri Wulandari; Radjali Amin; I Gde Adi Suryawan Wangiyana (Jurnal Penelitian Hasil Hutan, 2025)
The world’s demand for wood is increasing while the amount of solid wood production is decreasing with the depletion of forests due to illegal logging and conversion of forest functions as plantation land. To overcome these problems, it is necessary to do the efficiency of wood raw materials so that the use of solid wood can be reduced. One of the efficient ways to use wood raw materials is to utilize optimized wood industrial waste by combining one or more types of wood which are glued together into a single unit, commonly called a laminated board. In this study, we will look at the effect of different types of wood and the weight of the glue spread on the resulting laminated board. Advantages Laminate board can produce a board size that is wide and long as needed because the joints are made as long as needed. In the manufacture laminated boards are made with the type of wood, namely jati putih (Gmelina arborea. Roxb), bajur (Pterospermum javanicum), sengon (Paraserianthes falcataria) and mixtures (jati putih, bajur and sengon) and the glue spread factor is 150 g and 200 g. Then the physical and mechanical properties were tested. The test results showed that the wood type had a significant effect on all physical and mechanical properties except for the thickness shrinkage and MoE tests. The interaction of the lamination glue spread factor and the wood type factor did not significantly affect all physical and mechanical properties of mixed wood waste laminated boards. Based on the test results, laminated board is classified as strong class III which can be used as a lightweight construction material indoors.